Comovement of Newly Added Stocks with National Market Indices: Evidence from Around the World - Claessens, Stijn; Yafeh, Yishay (Review of Finance, 2013)
Abstract We document increased stock price comovement for companies added to major indices around the world. Using data on forty developed and emerging markets for 10 years, we find that in most markets, when added to a major index, firms experience an increase in their beta (especially if their pre-inclusion beta is low) and in the extent to which market returns explain firm stock returns (R2). Stock turnover and analyst coverage also typically increase upon inclusion. Various empirical tests suggest that the category/habitat views of Barberis, Shleifer and Wurgler explain most of these results, although information-related factors also account for some findings.